A new species of dartfish of the genus Ptereleotris (Teleostei: Gobiidae) from the East Coast of India - Kodeeswaran, P.; Praveenraj, J. (Zootaxa, 2020)
Ptereleotris cyanops n. sp. is described from five specimens collected in trawl landings at Chennai, Tamil Nadu, East Coast of India. The new species is unusual among congeners in possessing a wide interdorsal space, its width 2.5–3.2% in SL. The new species resembles P. microlepis in general morphology and coloration, but is readily distinguished from it in lacking a black bar at base of pectoral fin, in having a slightly truncate caudal fin with the 5th and 13th branched rays prolonged as filaments (vs. emarginated caudal fin with absence of any caudal filaments), and in having the second dorsal and anal fin not elevated anteriorly (vs. elevated). Ptereleotris cyanops differs from caudal filaments bearing congeners viz., P. arabica and P. hanae, by the absence of chin barbel (vs. present in both); in having a longer pelvic fin (17.7–18.8 vs. 13.1–15.5% SL in P. arabica), and more anal rays (27 vs. 22–25 in P. hanae).